Mitigation strategies for pandemic influenza - Stephen Clarence. (2012)
Highly pathogenic viruses like the H1N1 and, SARS have hit Singapore hard, causing many people to fall ill to them. Human cases of fatality have also been unfortunately reported. Utilising software provided from America’s Centers for Disease Control and Prevention (CDC), we present a review of literature of influenza modeling and discuss how the effectiveness of the 3 non- pharmaceutical interventions; school closure, usage of face mask and quarantine. One pharmaceutical mitigation strategy; vaccines was studied. We also use the relevant information for 3 viruses- a generic virus, influenza A H1N1 and an estimated influenza A H5N1 with the capability for human-human transmission for simulation to see how the mitigation strategies match up to the different characteristics of the viruses. By reviewing the results obtained, we find that none of the mitigation strategies can delay the peak of the influenza impact. The best result of mitigation is obtained when face masks are used not more than 3 days after symptoms appear and at least 74% of the population must be using it for the effectiveness of such a mitigation strategy to be sought out. School closure would be most effective if it is at least 14 days and the cumulative incidence had to be below 1% for it to be rendered as a good mitigation strategy. Quarantine was best at 15 days, however it is very disruptive to our daily living, 10 days was proposed and if more than 50% of the proposed cases are quarantined, it would be deemed as effective.